Slope Deformation of Road Shoulder and Retaining Wall Evaluation at Rancacili- Rancasari Road, West Jawa - Prattama, Febbry; Kamaludin, Rifan; Febriyanto, Feri; Adam, Jamalludin; Agustian, Yanyan (International Journal of Psychosocial Rehabilitation, 2020)
amage that is often found on the road is the collapse of the shoulder of the road even worse is the slope of the shoulder and this can be caused by the bearing capacity of the road that is not sufficient to withstand the live load that passes through the road and this is compounded by the absence of retaining walls on the slope. The Rancacili-Rancasari road section is a national alternative road that many vehicles pass by. In some places on the road, cracks occur and land subsidence occurs which can cause landslides on the shoulder of the road. The objective of this study is to evaluate the use of retaining walls to overcome landslides on the shoulder of the road. Taking into account the properties of the soil and the properties of the soil in the area, as an input parameter calculation, an appropriate and safe desgn is determined for the retaining wall type of self-weight retaining wall. By using the basic theory of earth pressure coloumb’s theory, a lateral pressure calculation is performed that works on the wall and combined with the trial wedge of lateral pressure theory, then calculates the total load received by the wall to find the safety factor of the wall relationship with resistance to rotation, sliding and its bearing capacity.